An Examination of Intervention Research with Secondary Students with EBD in Light of Common Core State Standards for Mathematics. (May 2014) - Mulcahy, Candace A.; Maccini, Paula; Wright, Kenneth; Miller, Jason
In this review, the authors offer a critical analysis of published interventions for improving mathematics performance among middle and high school students with EBD in light of the Common Core State Standards. An exhaustive review of literature from 1975 to December 2012 yielded 20 articles that met criteria for inclusion. The authors analyzed the body of research for the nature of participants, settings, interventionists, interventions, and alignment with Common Core State Standards. Despite limitations with the body of research, the results of the review indicate a number of promising practices exist for secondary students with EBD in mathematics, including: (a) peer-mediated approaches, (b) interventions that address academic performance as well as behavior, (d) use of technology, and (e) use of strategy instruction to support conceptual understanding. Implications for research and practice are provided.